A cross-sectional national survey assessing self-reported drug intake behavior, contact with the primary sector and drug treatment among service users of Danish drug consumption rooms. Issue 1 (December 2016) - Toth, Eva; Tegner, Jette; Lauridsen, Sigurd; Kappel, Nanna
Abstract Background Drug consumption rooms (DCRs) have been implemented worldwide as a harm-reducing strategy. In 2012, Denmark passed legislation allowing establishment of DCRs. The aim of this study was to identify characteristics and gain knowledge of the way service users use the DCRs including bridge building to specialized health care. Associations between nationality, opioid substitution treatment (OST), drug intake method, and response to staff advice on harm-reducing education was investigated, as well as service user's reasons for using the DCRs, and their perceptions of safety and trust in the DCRs. Methods A survey questionnaire sampled 154 participants of DCRs. Convenience sampling was used. Key variables covered demographics, drug intake mode, educational advice received in the DCR, and opinions about and role of the DCRs for the service users. Results Only 10 % of the participants were under the age of 30, 30 % between 30 and 39 years, 36 % between 40 and 49 years, and 24 % age 50 or more. A total of 60 % of the participants had encountered drugs before they were 19 years old. Female participants were 25 %, and 73 % were Danish citizens, 8 % were non-Danish EU citizens, and 18 % were non-EU citizens. As drug intake method, 63 % injected drugs in a vein, 7 % sniffed, and 37 % smoked. Of drugs used in the DCR, 49 % used cocaine, 41 % heroin, 16 % a mix of heroin and cocaine, and 16 % used methadone. Participants who smoked drugs made significantly less use of drug rehabilitation than participants who sniffed or injected drugs. There was a similar rate of advice on OST across nationality. Participants accepted staff education on hygienic measures and safe injection practices and found it useful. Participants felt safe and trusted staff and bridge building to specialized health care took place in the DCR. Conclusions Staff of Danish DCRs educate service users on health related issues and harm-reducing interventions. A subgroup who smoke and a subgroup of nationality other than Danish are underserved and have less likely been in OST. More research on these groups is needed.